Approximation of continuous signals in the environments of Mattetasa and MatLab / Simulink Integrated Systems - Васильєв, В. В.; Сімак, Л. О.; Тодорова, Г. М. (Proceedings of National Aviation University (archive), 2021)
The problem of approximation of continuous signals by generalized polynomials with the help of the modified method of equal areas is considered. It is shown that the use of this method leads to simpler hardware solutions and reduces the computational resources costs. The illustration is made in the integrated environments of Mattematika and MatLab